Girls with a History of Premature Adrenarche Have Advanced Growth and Pubertal Development at the Age of 12 Years - Liimatta, Jani; Utriainen, Pauliina; Voutilainen, Raimo; Jääskeläinen, Jarmo (Frontiers in Endocrinology, 2017)
Background: Premature adrenarche (PA) has been linked with early thelarche and menarche, but longitudinal data on growth and pubertal development after PA are insufficient. Methods: Growth and pubertal development of mostly full-term and appropriate for gestational age -born 43 PA (36 girls) and 63 control children (52 girls) were analyzed prospectively. Children examined first at the mean age of 7.6 years were re-examined at the mean age of 12.0 years. Results: The PA girls but not the boys were taller and had higher body mass index than the controls. A higher proportion of the PA than control girls had reached menarche, while the same percentage of the PA and control boys were at Tanner genital stage ≥ 2. The PA girls with premature pubarche (PP) were taller but not heavier and had more often reached menarche by the age of 12 years than the PA girls without PP. The PA girls with menarche had lower birth length and higher prepubertal insulin-like growth factor 1 (IGF-1) concentrations compared to non-menarcheal PA girls. In logistic regression analyses for all girls, lower birth length standard deviation score, earlier maternal menarche, and higher prepubertal IGF-1 were independently associated with menarche. Conclusions: At 12 years of age, the PA girls had higher body mass index, advanced linear growth, and accelerated pubertal development with earlier menarche than the control girls. The PA girls with PP were taller and had earlier menarche than the PA girls without PP. Lower birth length and higher prepubertal IGF-1 concentration were predictive factors for menarche by the age of 12 years.